Polyphenyl ether resin, preparation method thereof, polyphenyl ether resin composition and application
The polyphenylene ether resin prepared by oxidative polymerization controls the molecular weight distribution and hydroxyl content, solving the problem of high moisture absorption rate of the polyphenylene ether resin composition in humid and heat environment, and achieving a combination of low saturation water absorption rate and excellent mechanical properties.
Patent Information
- Application Number
- CN202411661318.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-07
AI Technical Summary
The existing polyphenylene ether resin composition is prone to high moisture absorption rate under humid and heat conditions, resulting in unstable size of the resin parts during long-term use and deterioration of water and temperature resistance.
Polyphenylene ether resin is prepared by oxidative polymerization, and the absolute molecular weight distribution is controlled, so that the mole proportion of polymer chains with an absolute molecular weight of 0-10,000 is 5-40%, and the hydroxyl content is reduced by devolatilization treatment to achieve the goal of low saturation water absorption.
The low saturation water absorption rate of the polyphenylene ether resin composition is achieved, which is less than 0.5%, which maintains excellent mechanical properties and broadens its application scenarios in humid and heat environments.
Smart Images

Figure BDA0005143432350000021 
Figure BDA0005143432350000031 
Figure BDA0005143432350000032
Abstract
Description
Technical Field
[0001] The present invention relates to the field of polyphenylene ether resin, and in particular to a polyphenylene ether resin and a preparation method thereof, and a polyphenylene ether resin composition and application thereof. Background Art
[0002] Polyphenyl ether obtained by polymerization with 2,6-dimethylphenol as monomer, as one of the five major engineering plastics, has broad application scenarios in electronic appliances, photovoltaics, new energy vehicles, water treatment devices and other fields. Due to the excellent low moisture absorption and good dimensional stability of polyphenyl ether, the modified polyphenyl ether resin is used as the main material of new energy battery brackets and photovoltaic junction boxes, and the market demand is increasing year by year.
[0003] The reason for the low moisture absorption rate of polyphenylene ether is that, from a structural analysis, the hydroxyl group at the end of the polyphenylene ether molecular chain is removed, and there is no large polar group in the main chain, as well as the hydrolysis group, which leads to a lower moisture absorption rate of the polyphenylene ether itself. Therefore, reducing the content of polar groups such as hydroxyl groups in the polyphenylene ether resin can theoretically reduce the saturated water absorption rate of the polyphenylene ether resin.
[0004] Chinese patent CN101103414B describes a method for preparing polyphenylene ether resin. The wet powder obtained by post-treatment contains a high moisture content, which will cause huge energy consumption in the subsequent drying process. In addition, there are residual undesirable solvents on the surface of the powder, which can easily affect the product quality.
[0005] Chinese patent CN1117683346A discloses a polyphenylene ether resin composition. The polyphenylene ether is mixed with a SEBS compound. Due to the addition of epoxy resin, the component contains more polar groups, resulting in a moisture absorption rate of the polyphenylene ether resin of more than 15%, which is not conducive to the long-term use of the resin under hot and humid conditions.
[0006] Chinese patent CN117683346A discloses a method for preparing a polyphenylene ether resin alloy, which introduces glass fiber and a toughening agent for modification, so that the saturated water absorption rate of the alloy is about 2.5%. However, the water and temperature resistance of the alloy will age and deform due to long-term high humidity and high heat conditions.
[0007] In summary, in the polyphenylene ether resin composition, polyphenylene ether is the main component, and the hydroxyl content needs to be further reduced so that the composition maintains a low water absorption rate, thereby broadening the application scenarios of the polyphenylene ether resin and maintaining the dimensional stability of the polyphenylene ether resin composition parts. Summary of the invention
[0008] In order to solve the technical problems existing in the prior art, the present invention provides a polyphenylene ether resin and a preparation method thereof. The polyphenylene ether resin has improved water absorption resistance of the polyphenylene ether resin composition while maintaining excellent mechanical properties after injection molding, and the saturated water absorption rate is less than 0.5%.
[0009] Another object of the present invention is to provide such a polyphenylene ether resin composition having low saturated water absorption.
[0010] Another object of the present invention is to provide an application of the polyphenylene ether resin composition having low saturated water absorption.
[0011] In order to achieve the above-mentioned invention object, the present invention adopts the following technical scheme:
[0012] A polyphenylene ether resin is prepared by oxidative polymerization and has a structure shown in formula (1):
[0013]
[0014] Wherein R1, R2, R3, and R4 are independently selected from any one of H, halogen, alkyl having 1 to 10 carbon atoms, alkoxy having 1 to 10 carbon atoms, aryl, halogen-substituted aryl, and alkenyl. Preferably, R1, R2, R3, and R4 are methyl, methyl, H, and H, respectively.
[0015] In one embodiment of the present invention, the molar proportion of polymer chains with an absolute molecular weight of 0-10000 in the polyphenylene ether resin is 5-40%, for example 10%, 15%, 20%, 25%, 30%, 35%, 40%, etc., preferably 10-30%, more preferably 15-20%, and the molar proportion of polymer chains with an absolute molecular weight of 25000-50000 is 60-90%, for example 60%, 65%, 70%, 75%, 80%, 85%, 90%, etc., preferably 65-98%, more preferably 85-95%.
[0016] In one embodiment of the present invention, the hydroxyl content of the polyphenylene ether resin is 0.01-100 μmol / g, for example, 1 μmol / g, 5 μmol / g, 10 μmol / g, 20 μmol / g, 30 μmol / g, 40 μmol / g, 50 μmol / g, 60 μmol / g, 70 μmol / g, 80 μmol / g, 90 μmol / g, 100 μmol / g, etc., preferably 1-40 μmol / g, more preferably 20-30 μmol / g.
[0017] In one embodiment of the present invention, the intrinsic viscosity of the polyphenylene ether resin is 0.20 to 0.90 dL / g, for example, 0.20 dL / g, 0.30 dL / g, 0.40 dL / g, 0.50 dL / g, 0.60 dL / g, 0.70 dL / g, 0.80 dL / g, 0.90 dL / g, etc., preferably 0.25 to 0.60 dL / g.
[0018] Another aspect of the present invention is a method for preparing a polyphenylene ether resin, the method comprising the following steps:
[0019] S1. Into a mixture of amine compounds, metal ions, phenolic compounds, and aromatic hydrocarbon solvents, an oxygen-containing gas is introduced to carry out polymerization reaction to obtain a polyphenylene ether resin solution;
[0020] S2, adding an aqueous solution of a metal ion chelating agent to the polyphenylene ether resin solution obtained in S1, so that the metal ions in the catalyst are complexed with the chelating agent and enter the aqueous phase, and obtaining a polyphenylene ether solution free of metal ions by liquid-liquid separation;
[0021] S3, mixing the polyphenylene ether resin solution obtained in S2 with a poor solvent for polyphenylene ether to precipitate the polyphenylene ether in a solid form;
[0022] S4, devolatilizing the solid obtained in S3 to obtain a polyphenylene ether resin.
[0023] In one embodiment of the present invention, the phenolic compound described in S1 has a structure shown in formula (II), wherein R1, R2, R3, and R4 can be independently selected from any one of H, halogen, alkyl having 1 to 10 carbon atoms, alkoxy having 1 to 10 carbon atoms, aryl, halogen-substituted aryl, and alkenyl, preferably 2,6-dimethylphenol in which R1 and R2 are methyl and R3 and R4 are H.
[0024]
[0025] In one embodiment of the present invention, the metal ions in S1 include oxidative transition metal ions such as chromium, manganese, cobalt, copper, etc., and the amine compounds include one or more of diamine compounds, tertiary monoamine compounds, and secondary monoamine compounds, wherein the diamine compounds are selected from one or more compounds having the general structural formula of formula (III),
[0026]
[0027] Among them, R1, R2, R4, and R5 each independently represent H, a straight-chain or branched alkyl group having 1 or more carbon atoms, R1, R2, R4, and R5 can have at most 2 H at the same time, and R3 is a saturated alkyl group having 2 or more carbon atoms.
[0028] In one embodiment of the present invention, the metal ion in S1 is Cu obtained by the reaction of hydrohalic acid and Cu2O. +solution, the hydrohalic acid is preferably HBr, the amine compound is composed of a diamine compound, a secondary monoamine compound, and a tertiary monoamine compound, for example, N,N-diisopropylethylenediamine, dipropylamine, and N,N-dimethylbutylamine; the molar ratio of the metal ion to the diamine compound, the secondary monoamine compound, and the tertiary monoamine compound is 1:(0.01-20):(0.1-50):(0.5-100), for example, 1:1:1:1, 1:5:10:20, 1:10:20:50, 1:15:40:80, etc.
[0029] In another aspect of the present invention, a polyphenylene ether resin composition is prepared by blending and modifying the aforementioned polyphenylene ether resin or the polyphenylene ether resin obtained by the aforementioned preparation method with other plastics; preferably, it is blended and modified with one or more of HIPS, PS, PA, ABS, PP, and PPS to obtain a resin composition.
[0030] In the present invention, the saturated water absorption rate of the injection-molded product is less than 0.5%.
[0031] In another aspect of the present invention, the use of the aforementioned polyphenylene ether resin composition in the processing of injection molded polyphenylene ether products is preferably used for injection molding of photovoltaic junction boxes, new energy battery brackets, and home appliance electronic control housings.
[0032] Compared with the prior art, the present invention has the following technical effects:
[0033] The molar proportion of polymer chains with an absolute molecular weight of 0-10000 in the polyphenylene ether resin of the present invention is as low as 9%, so that the saturated water absorption rate of the injection-molded parts of the polyphenylene ether resin is less than 0.5% while having excellent mechanical properties.
[0034] The method of the present invention can achieve controllable molecular weight through process control, and achieve a low molecular weight of 0-10000 g / mol in the polyphenylene ether resin of 5-40%, preferably as low as 9%, which can significantly improve the saturated water absorption rate of the material, thereby broadening the application scenarios of the polyphenylene ether resin and maintaining the dimensional stability of the polyphenylene ether resin composition parts. DETAILED DESCRIPTION
[0035] In order to better understand the technical solution of the present invention, the following examples will further illustrate the method provided by the present invention, but the present invention is not limited to the listed examples, and should also include any other known changes within the scope of the claims of the present invention.
[0036] According to the analysis rules of matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF), the molecular ion peaks appearing in the spectrum correspond to the absolute molecular mass of the polymer. The detector acceptance range is set to 0-50000, and a cluster of polyphenylene ether molecular ion peaks with different polymerization degrees are obtained. The intensity of each peak corresponds to Di , the corresponding mass-to-charge ratio is m i , then the hydroxyl concentration c in the polyphenylene ether resin can be calculated according to formula (1).
[0037]
[0038] The present invention is further explained below by more specific examples, but does not constitute any limitation.
[0039] The sources of raw materials used in the following examples and comparative examples are as follows:
[0040] 2,6-Dimethylphenol, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99%;
[0041] 2,6-Diethylphenol, Shanghai Aladdin Biochemical Technology Co., Ltd., purity>99%;
[0042] 2,6-Dimethylphenylphenol, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99%;
[0043] N,N-diisopropylethylenediamine, Shanghai Longsheng Chemical Co., Ltd., purity>98%;
[0044] N,N-di-tert-butylethylenediamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99%;
[0045] Dipropylamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >98%;
[0046] N,N-diethylethylenediamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99%;
[0047] Dimethylbutylamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >98%;
[0048] Triethylamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity> 98%
[0049] Dipropylamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >98%;
[0050] Dipentylamine, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >98%;
[0051] Cu2O, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >98%;
[0052] Toluene, Yantai Yuandong Fine Chemical Co., Ltd., purity >99%;
[0053] Chlorobenzene, Shanghai Denuo Chemical Co., Ltd., purity >99%;
[0054] Methanol, Shanghai Aladdin Biochemical Technology Co., Ltd., purity >99%;
[0055] Chloroform, GREAGENT Co., Ltd., purity >98%;
[0056] 40% HBr, GREAGENT Co., Ltd., purity > 98%;
[0057] Ethylenediaminetetraacetic acid tetrasodium salt (EDTA·4Na), GREAGENT Co., Ltd., purity >98%;
[0058] Nitrilotriacetic acid trisodium salt, GREAGENT Co., Ltd., purity >98%.
[0059] Number average molecular weight, measured by size exclusion gel chromatography using PS or pre-calibrated, instrument manufacturer: Agilent Technologies, column model: PLgel 5μm .
[0060] The intrinsic viscosity is tested by Ubbelohde viscometer, instrument manufacturer: Hangzhou Zhuoxiang Technology Co., Ltd., instrument model: AVM-4.
[0061] The absolute molecular weight composition and hydroxyl content in the resin composition were directly and indirectly measured by MALDI-TOF.
[0062] The volatile content is determined by liquid chromatography methods known to those skilled in the art.
[0063] Example 1
[0064] This embodiment provides a method for preparing a polyphenylene ether resin, comprising the following steps:
[0065] In a 30L reactor equipped with a stirring device, 3000.25g (24.56mol) of 2,6-dimethylphenol, 11967.8g of toluene, 4.32g (0.03mol) of N,N-diisopropylethylenediamine, 17.19g (0.17mol) of dipropylamine, 31.35g (0.31mol) of triethylamine, 20.23g (0.10mol) of HBr and 1.43g (0.01mol) of Cu2O were added in sequence, stirred and mixed, and heated to 50°C. Oxygen was introduced at a flow rate of L / min, and the reaction was carried out at 25±5°C for 40 minutes. After the polymerization was completed, 200 g (0.02 mol / L) of an aqueous solution of trisodium nitrilotriacetic acid was added, and the mixture was stirred at 55±5°C for 60 minutes. 1000 mL of deionized water was added and allowed to stand for stratification to obtain a toluene solution from which copper ions were removed. The toluene solution was mixed with methanol to obtain a solid polyphenylene ether wet powder. After vacuum drying at 120°C, a polyphenylene ether resin 1 having a hydroxyl content of 31 μmol / g and an intrinsic viscosity of 0.42 dL / g was obtained.
[0066] Example 2
[0067] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 3689.40 g (24.56 mol) of 2,6-diethylphenol, 14561.3 g of chlorobenzene, 7.21 g (0.05 mol) of N,N-diisopropylethylenediamine, 55.62 g (0.55 mol) of dipropylamine, and 696.72 g (6.89 mol) of dimethylbutylamine, and finally a polyphenylene ether resin 2 with a hydroxyl content of 26 μmol / g and a characteristic viscosity of 0.45 dL / g was obtained.
[0068] Example 3
[0069] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 6044.22 g (24.56 mol) of 2,6-xylenolphenol, 11967.8 g of toluene, 5.17 g (0.03 mol) of N,N-di-tert-butylethylenediamine, 37.72 g (0.24 mol) of dipentylamine, and 322.57 g (3.19 mol) of dimethylbutylamine, and finally a polyphenylene ether resin 3 with a hydroxyl content of 29 μmol / g and a characteristic viscosity of 0.51 dL / g was obtained.
[0070] Example 4
[0071] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 3000.25 g (24.56 mol) of 2,6-dimethylphenol, 14561.3 g of chlorobenzene, 4.65 g (0.04 mol) of N,N-diethylethylenediamine, 91.01 g (0.90 mol) of dipropylamine, and 905.02 g (8.95 mol) of dimethylbutylamine, and the temperature during the polymerization was adjusted to 35±5°C, and finally a polyphenylene ether resin 4 with a hydroxyl content of 21 μmol / g and a characteristic viscosity of 0.39 dL / g was obtained.
[0072] Example 5
[0073] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 3689.40 g (24.56 mol) of 2,6-diethylphenol, 14561.3 g of chlorobenzene, 15.86 g (0.11 mol) of N,N-diisopropylethylenediamine, 86.45 g (0.55 mol) of diamylamine, and 464.14 g (4.59 mol) of dimethylbutylamine, and after the chelating agent was added, the system temperature was controlled at 65±5°C, and finally a polyphenylene ether resin 5 with a hydroxyl content of 41 μmol / g and an intrinsic viscosity of 0.30 dL / g was obtained.
[0074] Example 6
[0075] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 6044.22 g (24.56 mol) of 2,6-xylenolphenol, 14561.3 g of chlorobenzene, 17.42 g (0.15 mol) of N,N-diethylethylenediamine, 112.24 g (1.11 mol) of dipropylamine, and 996.03 g (9.85 mol) of triethylamine. The chelating agent was an aqueous solution of tetrasodium salt of ethylenediaminediacetic acid. The added molar amount and concentration were the same as those in Example 1. Finally, a polyphenylene ether resin 6 with a hydroxyl content of 24 μmol / g and a characteristic viscosity of 0.43 dL / g was obtained.
[0076] Comparative Example 1
[0077] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 14561.3 g of chlorobenzene, 10.33 g (0.06 mol) of N,N-di-tert-butylethylenediamine, 36.15 g (0.23 mol) of diamylamine, and 78.87 g (0.78 mol) of dimethylbutylamine, and other conditions were exactly the same. Finally, a polyphenylene ether resin A1 with a hydroxyl content of 10 μmol / g and a characteristic viscosity of 0.55 dL / g was obtained.
[0078] Comparative Example 2
[0079] The experiment was carried out according to the method of Example 1. The difference from Example 1 was that the composition of the polymerization solution was adjusted to 2.32 g (0.02 mol) of N,N-diethylethylenediamine, 324.60 g (3.21 mol) of dipropylamine, and 160.78 g (1.59 mol) of triethylamine, and the other conditions were exactly the same. Finally, a polyphenylene ether resin A2 with a hydroxyl content of 49 μmol / g and an intrinsic viscosity of 0.29 dL / g was obtained.
[0080] The polyphenylene ether resin prepared in the above embodiments and comparative examples was extruded with HIPS and PPS at a mass ratio of 50:40:10 through a twin-screw extruder at 320°C and 260rpm. The performance test results of the resin composition prepared after blending and modification are shown in the following table.
[0081]
[0082] It can be seen from the table that the absolute molecular weights of the polyphenylene ether resin polymer segments obtained by the preparation methods in Comparative Examples 1 and 2 are concentrated in the high molecular weight and low molecular weight ranges, respectively. Although the polyphenylene ether resin in Comparative Example 1 has a low saturated water absorption rate, the flexural strength of the polyphenylene ether resin mixture prepared therefrom is significantly reduced, which may be due to the reduced polarity and poor blending compatibility leading to phase separation of the composition, resulting in a significant reduction in flexural strength. In Comparative Example 2, the molecular weight below 10,000 accounts for more than 40%, resulting in an increase in the saturated water absorption rate, affecting all thermodynamic properties.
[0083] It can be seen from the table that controlling the absolute molecular weight distribution of the polyphenylene ether resin is beneficial to reducing the hydroxyl content of the polyphenylene ether resin and improving the thermodynamic properties of the polyphenylene ether resin composition.
[0084] Although the content of the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Those skilled in the art will appreciate that, under the guidance of this specification, some modifications or adjustments may be made to the present invention. These modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. A polyphenylene ether resin prepared by oxidative polymerization, characterized in that: The molar proportion of polymer chains with an absolute molecular weight of 0-10000 in the polyphenylene ether resin is 5-40%, the molar proportion of chain segments with an absolute molecular weight of 25000-50000 is 60-90%, and the hydroxyl concentration in the polyphenylene ether resin is 0.01-100 μmol / g.
2. The polyphenylene ether resin according to claim 1 has a structure as shown in formula (I), Wherein R1, R2, R3, and R4 are independently selected from any one of H, halogen, alkyl with 1 to 10 carbon atoms, alkoxy with 1 to 10 carbon atoms, aryl, halogen-substituted aryl, and alkenyl; preferably, R1, R2, R3, and R4 are methyl, methyl, H, and H, respectively.
3. The polyphenylene ether resin according to claim 1 or 2, characterized in that The molar proportion of polymer chains with an absolute molecular weight of 0-10,000 is 5-30%, preferably 5-10%, and the molar proportion of polymer chains with an absolute molecular weight of 25,000-50,000 is 70-85%, preferably 75-80%.
4. The polyphenylene ether resin according to claims 1-3, characterized in that: The intrinsic viscosity of the polyphenylene ether resin is 0.20 to 0.90 dL / g, preferably 0.25 to 0.60 dL / g; Preferably, the hydroxyl content of the polyphenylene ether resin is 0.01-40 μmol / g, preferably 20-30 μmol / g.
5. A method for preparing the polyphenylene ether resin according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1, introducing oxygen-containing gas into a mixture of amine compounds, metal ions, phenolic compounds, and aromatic hydrocarbon solvents to carry out polymerization reaction to obtain a polyphenylene ether resin solution; S2, adding an aqueous solution of a metal ion chelating agent to the polyphenylene ether resin solution obtained in S1, so that the metal ions in the catalyst are complexed with the chelating agent and enter the aqueous phase, and obtaining a polyphenylene ether solution free of metal ions by liquid-liquid separation; S3, mixing the polyphenylene ether resin solution obtained in S2 with a poor solvent for polyphenylene ether to precipitate the polyphenylene ether in a solid form; S4, devolatilizing the solid obtained in S3 to obtain a polyphenylene ether resin.
6. The preparation method according to claim 5, characterized in that: The phenol compound described in S1 is as shown in formula (II), wherein R1, R2, R3, and R4 can be independently selected from any one of H, halogen, alkyl having 1 to 10 carbon atoms, alkoxy having 1 to 10 carbon atoms, aryl, halogen-substituted aryl, and alkenyl, preferably R1 and R2 are methyl, and R3 and R4 are 2,6-dimethylphenol, 7. The preparation method according to claim 5, characterized in that: The metal ion is an oxidative transition metal ion selected from any one of chromium, manganese, cobalt and copper; and / or The amine compound is selected from one or more of diamine compounds, tertiary monoamine compounds, and secondary monoamine compounds. Preferably, the diamine compound is selected from one or more compounds having the general structural formula of formula (III); Among them, R1, R2, R4, and R5 each independently represent H, a straight chain or branched alkyl group with a carbon number of 1 or more, R1, R2, R4, and R5 can have at most 2 H at the same time, and R3 is a saturated alkyl group with a carbon number of 2 or more.
8. The preparation method according to claim 7, characterized in that: The metal ion is from CuBr; the amine compound is composed of a diamine compound, a secondary monoamine compound, and a tertiary monoamine compound; Preferably, the molar ratio of the metal ion to the diamine compound, the secondary monoamine compound, and the tertiary monoamine compound is 1:(0.01-20):(0.1-50):(0.5-100); More preferably, the CuBr is prepared by reacting HBr with Cu2O.
9. A polyphenylene ether resin composition, characterized in that Prepared by blending and modifying the polyphenylene ether resin described in any one of claims 1 to 4 or the polyphenylene ether resin prepared by the preparation method described in any one of claims 5 to 8 with other plastics; Preferably, the polyphenylene ether resin is blended and modified with one or more of HIPS, PS, PA, ABS, PP, and PPS to obtain a polyphenylene ether resin composition; More preferably, the saturated water absorption rate of the injection molded part is less than 0.5%.
10. The use of the polyphenylene ether resin composition according to claim 10 in the processing of injection-molded polyphenylene ether products, preferably for injection molding photovoltaic junction boxes, new energy battery brackets, and home appliance electronic control housings.
Citation Information
Patent Citations
Inner part of hard disk drive, resin composition for inner part of harddisk drive, and manufacture method of resin composition
CN101103414B
Low-water-absorption glass fiber reinforced PA / PPO alloy and preparation method thereof
CN117683346A
Polyphenylene ether and manufacturing method thereof
CN110387037A
Preparation method of high-purity low-molecular-weight dihydroxy polyphenyl ether
CN113980265A
Low-quinone-content polyphenyl ether resin and preparation method thereof
CN117143330A